How Do Local Governments cope with COVID-19? Comparative Experiences in Three Southeast Asian Cities - Ridho Al-Hamdi; Halimah Abdul Manaf; Non Naprathansuk; Alim Bubu Swarga (Universitas Muhammadiyah Yogyakarta, 2022)
This paper is aimed to investigate strategies of Southeast Asian local governments in addressing the COVID-19 situation by applying the framework of good governance principles and, in turn, to figure out the determinant factor of the successful strategy in each country. It is qualitative research by applying multiple cases of three cities in Southeast Asian countries, i.e., Indonesia, Malaysia, and Thailand. For data gathering, it takes relevant sources of News channels, whether in English or local languages of those countries. The finding demonstrates that Indonesia, Malaysia, and Thailand can adopt all principles of good governance in addressing the COVID-19 pandemic situation. Nevertheless, each country has its determinant factor of the successful strategy in handling a such situation. Indonesia is more excellent in the implementation of transparency, Malaysia has a well performance in the operation of participation, while Thailand is more successful in the application of accountability. These depict that each state has a typical strategy in coping with this global pandemic situation.